The Evolving Legal Mechanism for Medical Malpractice Dispute Resolution in China - Lin, Nuannuan; Hu, Weijun (Columbia Journal of Asian Law, 2018)
This Article investigates the evolution of the Chinese legal mechanism for medical malpractice dispute resolution (MMDR) from the establishment of the first rules for MMDR in 1955 to the promulgation of the Regulation on Preventing and Dealing with Medical Malpractice Disputes in 2018. Using historical documents and chronicled sources, it reveals the politicization of adverse events in the 1950s-70s and explores how the unique historical and political context created a different philosophical and practical foundation for the Chinese mechanism for MMDR. In contrast to the common law position that treats medical malpractice as a breach of the duty of care to patients, the Chinese mechanism treated medical malpractice as a breach of duties which a health care professional owed to the health administration system. In comparison with the common law approach that allocates medical malpractice cases to private law, the Chinese approach allocated medical malpractice cases to an administrative-led dispute resolution system. That is why, as this article explains, the Chinese MMDR mechanism focused on disciplinary and regulatory functions rather than the function of redressing damages in the early stages of its development. This early philosophical and practical foundation was altered by the Chinese economic and health system reforms initiated in 1978 and 1985. As the reforms transformed patients into consumers of health services, pecuniary compensation became an unavoidable issue for the MMDR mechanism. The article then tracks changes in the laws and regulations governing medical malpractice disputes during 1987-2018 and takes judicial practice into account when explaining how the MMDR mechanism shifts its legitimacy from one based on health administrative rules to one based on the Chinese civil laws and shifts its function from deterring medical malpractice to compensating for medical injuries. The results of this research shed light on the social dynamics of legal reform, suggesting that the evolution of the Chinese legal mechanism may be understood as a dynamic product of an ongoing interaction between law and society.